EFFECT OF SMOKING CESSATION AND BIOMASS FUEL EXPOSURE PREVENTION ON QUALITY OF LIFE IN COPD PATIENTS IN QUETTA, PAKISTAN (Journal of Medical & Health Sciences Review, 2025)
Background: COPD limits patients' quality of life (QoL) through two major contributing factors which are tobacco smoke exposure and exposure to biomass fuel emissions. The key step to enhance COPD patient outcomes starts with preventing biomass fuel exposure along with smoking cessation. This study investigates the effect of these interventions on the QoL of COPD patients in Quetta, Pakistan.Aims/Objectives: Researchers evaluated the effects of smoking cessation programs together with biomass fuel prevention strategies on patient quality of life for COPD patients in Quetta Balochistan Pakistan while identifying local issues that affect gender equality and cultural differences and patient follow-up with interventions.Research Methodology: The research consisted of hospital observations performed from December 2024 to February 2025 at three major hospitals (Bolan Medical Complex, Sandeman Provincial, and Fatima Jinnah General & Chest Hospital’s Quetta) in Quetta with 354 COPD patients participating. Data collection involved structured questionnaires alongside patient interviews and medical records investigation of demographic and respiratory symptoms smoking history fuel usage and healthcare visit information. The medical team diagnosed COPD through tests that included spirometry and both chest X-rays and CT scans. Data were analyzed using SPSS.Results: A significant proportion of 63.3% experienced COPD among male participants. Cough accompanied by sputum occurrence was reported by 42.09% of patients while dyspnea affected 29.38% of the respondents. Female patients demonstrated slightly higher smoking behavior at 55.1% than male patients who reported 53.6%. A large number of patients (39.83%) depended on biomass fuels before their diagnosis but only limited patients switched to cleaner fuels afterward.Conclusion: The prevention of biomass fuel exposure and smoking cessation stand as vital measures for enhancing QoL among patients who have COPD. The unique health problems affecting females compared to males along with local cultural norms and treatment compliance patterns in Balochistan Pakistan need specific intervention approaches to boost respiratory health results.